(untitled) (Applied Biological Research, 2024)
Seaweeds are potential renewable resources in marine environment. This study explored the biochemical composition of red seaweeds collected from the Gulf of Mannar, Tamil Nadu, India focussing on the species like Hypnea musciformis, Gracilaria salicornia, G. folifera, G. crassa and Jania rubens. The results showed that amongst the tested red seaweeds H. musciformis had highest carbohydrate content (28.21%), while G. salicornia had highest lipid content (3.89%). J. rubens contained the most protein (14.47%), whereas G. folifera had highest levels of chlorophyll a and flavonoids (20.1%). G. crassa had highest phenol content (7.91%) while ash content was higher in J. rubens (39.1%) and lower in G. salicornia (18.2%). Phycocyanin and allophycocyanin were maximum in G. crassa; whereas highest phycoerythrin was noticed in H. musciformis. Conversely, minimum phycobiliprotein pigments were found in G. salicornia and G. crassa. The findings highlighted the potential of these seaweeds for medicinal and industrial applications.